Le journalisme indien à la croisée des courants d'action journalistique - Demay, Joël (Anthropologica, 2022)
Notwithstanding four decades of journalistic practice, North American Indians in Canada and the United States have not formulated an analytical definition of their professional approach. This paper assesses the four major approaches to journalistic practice which currently influence the development of native journalism: western North American journalism, existential journalism, developmental journalism, and the traditional philosophy of social communication among native peoples.